The Role of Education and Knowledge Management in Stunting Prevention and Its Impact on Educational and Economic Factors (Survey in West Java) - Umi Narimawati; Dadang Munandar; Syahrul Mauluddin; Marliana Budhiningtias Winanti; Rangga Sidik (International Journal of Economics Development Research (IJEDR), 2023)
This research aims to see the influence of education and knowledge management on stunting prevention and its impact on educational and economic factors in West Java. In conducting research, the author used a quantitative approach, descriptive verification design and survey methods. A total of 100 activist mothers were used as respondents for this study. Path Analysis is used to analyze the data. The following are the results of the research: First, education and knowledge management have a significant influence on stunting prevention simultaneously. Second, education has a significant influence on partial prevention of stunting. Third, Knowledge Management has a significant influence on partial stunting prevention. Fourth, Stunting Prevention has a significant effect on Education and Economic Factors. Fifth, Education and Knowledge Management have a significant effect on Economic Factors through the mediation of Stunting Prevention. In general, it can be concluded that the role of education and knowledge management is useful in reducing the problem of stunting.